RETRACTED: Policy Evaluation Of The Pagar Dewa Village Head Of Pondok Kelapa District, Bengkulu Central District In The Use Of Village Funds In 2020 - Mirwansyah; Asnawati; Imanda, Antonio (Social Sciences Journal, 2024)
Following up on the review of articles published in the Social Sciences Journal carefully, carefully, and considering the article entitled "Policy Evaluation Of The Pagar Dewa Village Head Of Pondok Kelapa District, Bengkulu Central District In The Use Of Village Funds In 2020 " Vol 1 No 1 (2024). This paper was found to violate the Social Sciences Journal Publication principles and has been withdrawn.This article has been published in the journal Profesional.The document and its contents have been removed from the Social Sciences Journal, and reasonable efforts should be made to remove all references to this article.